2020
DOI: 10.1136/bmjqs-2019-010463
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of peripherally inserted central catheter use among general medical inpatients: an observational study using routinely collected data

Abstract: BackgroundPeripherally inserted central catheters (PICC) are among the most commonly used medical devices in hospital. This study sought to determine the appropriateness of inpatient PICC use in general medicine at five academic hospitals in Toronto, Ontario, Canada, based on the Michigan Appropriateness Guide for Intravenous Catheters (MAGIC).MethodsThis was a retrospective, cross-sectional study of general internal medicine patients discharged between 1 April 2010 and 31 March 2015 who received a PICC during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“… 10 In a study by investigators in Ontario, applying MAGIC to measure appropriateness of catheter use in a provincial database was found to be feasible with a substantial proportion of PICCs deemed either uncertain or inappropriate—suggesting room for improving quality of care. 20 Similarly, a national study of Medicare recipients found that the publication of MAGIC was associated with reductions in overall PICC use in the US. 21 The present study advances these findings by showing a significant association between PICC appropriateness and complications across multiple hospitals.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In a study by investigators in Ontario, applying MAGIC to measure appropriateness of catheter use in a provincial database was found to be feasible with a substantial proportion of PICCs deemed either uncertain or inappropriate—suggesting room for improving quality of care. 20 Similarly, a national study of Medicare recipients found that the publication of MAGIC was associated with reductions in overall PICC use in the US. 21 The present study advances these findings by showing a significant association between PICC appropriateness and complications across multiple hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Essa atitude favorece o desperdício do material por uso inadequado ou vencimento da validade. Pesquisadores recomendam intervenções direcionadas para reduzir o uso inadequado de PICC, considerando os custos e complicações potenciais associadas à colocação desse cateter (14) .…”
Section: Discussionunclassified
“…O uso do PICC por uma equipe de inserção especializada liderada por enfermeiras, com material de boa qualidade, uso protocolos para manutenção e cuidados e implementação das iniciativas de melhoria contínua de qualidade pode resultar em redução na incidência de complicações maiores, como infecções da corrente sanguínea relacionadas ao cateter e trombose venosa profunda (17;18) . Analisando 3479 colocações de PICC durante a hospitalização de pacientes de medicina interna geral, pesquisadores observaram que pouco mais da metade (53%) tiveram colocação totalmente adequada (14) .…”
Section: Competência De Enfermeiros Para Uso Do Cateter Central De Inunclassified
“…6 7 Furthermore, with the publication of the Michigan Appropriateness Guide for Intravenous Catheters (MAGIC) guidelines, the ability to examine appropriateness of PICC use at hospitals has emerged. [8][9][10][11] Findings from the USA, for example, have found that inappropriate use of PICCs often occurs in patients with chronic kidney disease (CKD) and in patients where PICCs are used for short duration, such as those with difficult venous access. Likewise, a study conducted by Verma et al in five academic hospitals in Toronto, Canada found that inappropriate PICC use most often occurred in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%